Small mercies : a novel [large type] - Lehane, Dennis (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
"One night Mary Pat's teenage daughter Jules stays out late and doesn't come home. That same evening, a young Black man is found dead, struck by a subway train under mysterious circumstances. The two events seem unconnected. But Mary Pat, propelled by a desperate search for her missing daughter, begins turning over stones best left untouched--asking questions that bother Marty Butler, chieftain of the Irish mob, and the men who work for him, men who don't take kindly to any threat to their business"--